Coating agent-induced mechanical behavior of 3D self-assembled nanocrystals. Issue 35 (22nd August 2017) - Çolak, Arzu; Wei, Jingjing; Arfaoui, Imad; Pileni, Marie-Paule
Abstract : The Young's modulus of three-dimensional self-assembled Ag nanocrystals, as so-called supracrystals, is correlated with the type of coating agent as well as the nanocrystal morphology. Abstract : The Young's modulus of three-dimensional self-assembled Ag nanocrystals, as so-called supracrystals, is correlated with the type of coating agent as well as the nanocrystal morphology. The Young's moduli of supracrystals of icosahedral Ag nanocrystals are measured in the range of tens to hundreds of megapascals revealing an extremely soft mechanical behavior. The alkylamine molecules used as coating agents weakly interact with the Ag nanocrystal surface favoring translational and orientational ordering of atomic lattice planes of nanocrystals. Under such experimental conditions, both the average distance between nanocrystals and the increase of the nanocrystal diameter control the measured Young's modulus: it increases with decreasing interparticle distance and increasing nanocrystal diameter. When dodecylamine (C12 NH2 ) molecules are replaced by dodecanethiol (C12 SH), the orientational ordering between nanocrystals, produced from the same batch as C12 NH2, disappears by inducing a drop in the Young's modulus. This is attributed to the formation of a "skin" at the nanocrystal surface causing a transition from shaped to spherical nanocrystals. Finally, by comparing with various studies performed in our group with Co and Au nanocrystals, we explain the formation of such extremely soft materials with Ag nanocrystals by both the strength of the binding between nanocrystals and coating agents and the ligand–ligand interactions.